MENINGKATKAN KEMAMPUAN MENULIS SISWA DALAM MENULIS DI FACEBOOK: INCREASING STUDENTS’ WRITING ABILITY TOWARDS WRITING ON FACEBOOK - Sartika, Ayu; Nurjannah, Lydia; Safitri, Yuslia; Ihsan, Muhammad Taufik (Education and Talent Development Center of Indonesia (ETDC Indonesia)., 2023)
The purpose of this study was to determine the effect of Facebook on students' English writing skills. Writing is one of the most important language components in learning English, because students' mastery of writing makes them understand the meaning of the written word. However, related to the current condition and situation, students in class still cannot write correctly and fluently in class. This causes them not to be interested in the lesson and they are bored with the way of learning that is just like that, monotonous and the absence of learning media in the learning process so that students feel bored and not interested in learning the lesson. Therefore, in this case using facebook. As we know, that Facebook has become one of the most commonly used social media to communicate with other people for various purposes. Because it allows people to share ideas through writing, Facebook is very likely to be used to facilitate language learning, especially to improve productive skills. In this article, we discuss how Facebook can act as a medium to improve students' skills or abilities in using Facebook. The teacher is someone who has an important role in the application of this technique in the classroom so that it can be applied properly. so that the teacher's role in the technique of using Facebook as a student learning medium must be in line so that it can be achieved properly.